A description of medical conditions in adults with autism spectrum disorder: A follow-up of the 1980s Utah/UCLA Autism Epidemiologic Study. (July 2016) - Jones, Kyle B; Cottle, Kristina; Bakian, Amanda; Farley, Megan; Bilder, Deborah; Coon, Hilary; McMahon, William M
This study describes medical conditions experienced by a population-based cohort of adults with autism spectrum disorder whose significant developmental concerns were apparent during childhood. As part of a 25-year outcome study of autism spectrum disorder in adulthood, medical histories were collected on 92 participants (N = 69 males) who were first ascertained as children in the mid-1980s, 11 of whom were deceased at the time of follow-up. Questionnaires queried medical symptoms, disorders, hospitalizations, surgeries, and medication use. Median age at follow-up was 36 years (range: 23.5–50.5 years), and intellectual disability co-occurred in 62%. The most common medical conditions were seizures, obesity, insomnia, and constipation. The median number of medical conditions per person was 11. Increased medical comorbidity was associated with female gender (p = 0.01) and obesity (p = 0.03), but not intellectual disability (p = 0.79). Adults in this cohort of autism spectrum disorder first ascertained in the 1980s experience a high number of chronic medical conditions, regardless of intellectual ability. Understanding of these conditions commonly experienced should direct community-based and medical primary care for this population.